The Role of Ecotourism in Environmental Conservation in the Kerujuk Area, North Lombok Regency - Putu Ayu Pratiwi Duta Siwantari; I Putu Gede; Teguh Hadisukarno (J-TRUE: Journal of Travel and Leisure, 2025)
Kerujuk ecotourism is located in the Menggala Village area, Pemenang District. In its development, the problems faced are related to human resources' ability to utilise the potential attractiveness of ecotourism. This study aims to examine the potential, explore internal and external factors that influence the development of ecotourism, and develop strategies for developing Kerujuk ecotourism. Data was collected through questionnaires, field observations, in-depth interviews, documentation, and Focus Group Discussions (FGD). This research approach uses qualitative methods and is analysed using: 1) IFAS and EFAS matrix analysis, which produces a general strategy (grand strategy) for developing Kerujuk ecotourism; 2) SWOT analysis that produces alternative strategies. The results of this study indicate that the general strategy that must be implemented in realising the development of Kerujuk ecotourism is a market penetration strategy and product development that is in quadrant V. Alternative strategies generated by the SWOT analysis in the development of Kerujuk ecotourism are maintaining and preserving the uniqueness of tourist attractions, increasing security and quality of service, improve the arrangement of tourist attractions, increase marketing activities by utilising information and communication technology, develop the potential of tourist attractions, improve the quality of competitiveness, develop ecotourism management, and improve the quality of human resources in the tourism sector